POWER-KNOWLEDGE RELATIONS IN THE FIELD OF POLITICAL ECOLOGY - LEFF,ENRIQUE (2017)
Abstract The current environmental crisis calls for thinking about the state of the world: the thermodynamic-ecological and symbolic-cultural conditions of organic and human life on the planet. In this regard, it stresses the need to realize the unawareness and life’s unsustainability that humanity has created. In this text I discuss and take a stand about some of the concepts and founding and constitutive research lines of political ecology. In this way I pretend to open dialogue by placing in context some of the principles, ideas, and founding viewpoints of political ecology in Latin America and contrasting them with those from the English-speaking school of thought. I intend not only to establish a political socio-geography, but to question the epistemic core of political ecology, and to stimulate a more cosmopolitan critical thinking in order to be able to face the hegemonic powers that lead the world into social and environmental decay